2018
DOI: 10.1039/c8nj01845f
|View full text |Cite
|
Sign up to set email alerts
|

Chiral separation and a molecular modeling study of eight azole antifungals on the cellulose tris(3,5-dichlorophenylcarbamate) chiral stationary phase

Abstract: Four immobilized polysaccharide-based chiral stationary phases have been examined for their enantioselectivity on azole analytes using normal phase liquid chromatography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…This year, the first modelling by docking of chloro‐substituted polysaccharide selectors have been reported. Indeed, enantioselection of eight azole antifungals (Table ) on the chlorinated cellulose tris (3,5‐dichlorophenylcarbamate) (CDCPC) has been modelled by Li and co‐workers by using molecular docking . The variation of the binding energies (average energy of the best cluster with the lowest docking energy) of the complexes formed by R ‐ and S ‐enantiomers was in agreement with the observed enantioselectivity under NP elution conditions (Table ).…”
Section: Polysaccharide Derivativesmentioning
confidence: 59%
See 1 more Smart Citation
“…This year, the first modelling by docking of chloro‐substituted polysaccharide selectors have been reported. Indeed, enantioselection of eight azole antifungals (Table ) on the chlorinated cellulose tris (3,5‐dichlorophenylcarbamate) (CDCPC) has been modelled by Li and co‐workers by using molecular docking . The variation of the binding energies (average energy of the best cluster with the lowest docking energy) of the complexes formed by R ‐ and S ‐enantiomers was in agreement with the observed enantioselectivity under NP elution conditions (Table ).…”
Section: Polysaccharide Derivativesmentioning
confidence: 59%
“…In Table , a summary of some representative docking and MD studies published in the period 2015‐2018 is reported . Firstly, in polysaccharides modelling, an important issue concerns the preparation of a built polymer which is representative of the ‘real’ polysaccharide derivative.…”
Section: Polysaccharide Derivativesmentioning
confidence: 99%
“…HPLC analysis is known to have a limitation in providing direct evidence of the specific binding sites of analytes with the chiral selector. On the other hand, computational docking offers further insights into the detailed geometry information and binding energy of the chiral selector-analyte complex [ 40 ]. Thus, computational docking has been proposed as simple approaches for understanding the chiral recognition mechanism on CSPs [ 41 , 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Retention factors k = (t R − t 0 )/t 0 were based on void times t 0 estimated from the earliest baseline perturbation as described by Zhu et al [49]. Resolution R s = (1.18 × (t R1 − t R2 ))/(w h1 + w h2 ) was calculated according to the European Pharmacopoeia from the difference of retention and the sum of peak width at half-height (w h ) [50].…”
Section: Methodsmentioning
confidence: 99%